Nucleotide sequence of the 2,3-dihydroxybiphenyl dioxygenase gene of Pseudomonas pseudoalcaligenes. - Furukawa, K (1987)
2,3-Dihydroxybiphenyl dioxygenase, which catalyzes ring metacleavage of 2,3-dihydroxybiphenyl, is encoded by the bphC gene of Pseudomonas pseudoalcaligenes KF707 (K. Furukawa and T. Miyazaki, J. Bacteriol. 166:392-398, 1986). We determined the nucleotide sequence of a DNA fragment of 2,040 base pairs which included the bphC gene. The fragment included one open reading frame of 912 base pairs to accommodate the enzyme. The predicted processed amino acid sequence of the enzyme subunit consisted of 302 residues, and its 12 NH2-terminal residues were in perfect agreement with those determined for the enzyme. Approximately 10 base pairs upstream from the initiation codon for 2,3-dihydroxybiphenyl dioxygenase, there was a base sequence complementary to the 3' end of the 16S rRNA from Pseudomonas aeruginosa. There was no promoterlike sequence in the region upstream of the bphC gene, but another long open reading frame was present. A putative bphD gene encoding a metacleavage compound-hydrolyzing enzyme was suggested in the region downstream of the bphC gene.